2012
DOI: 10.1016/j.conb.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Medullary circuits for nociceptive modulation

Abstract: Neurons in the medullary raphe are critical to opioid analgesia through descending projections to the dorsal horn. Work in anesthetized rats led to the postulate that nociceptive suppression results from tonic activation of nociceptive-inhibiting neurons and tonic inhibition of nociceptive-facilitating neurons. However, morphine does not cause tonic changes in raphe neuronal firing in unanesthetized rodents. Recent work suggests that a drop in activity of nociceptive-inhibiting neurons synchronizes nociceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 40 publications
0
22
0
2
Order By: Relevance
“…Pronociceptive and antinociceptive descending modulation from the RVM is mediated by activity of ON and OFF neurons, respectively (Fields et al, 1983; Fields and Heinricher, 1985; Mason, 2012). We have previously demonstrated that only ON cells were activated by iontophoretic application of an NK-1R agonist (Budai et al, 2007) suggesting that NK-1Rs are located mainly on subset of these pronociceptive neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pronociceptive and antinociceptive descending modulation from the RVM is mediated by activity of ON and OFF neurons, respectively (Fields et al, 1983; Fields and Heinricher, 1985; Mason, 2012). We have previously demonstrated that only ON cells were activated by iontophoretic application of an NK-1R agonist (Budai et al, 2007) suggesting that NK-1Rs are located mainly on subset of these pronociceptive neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are not affected by noxious cutaneous stimuli but may modulate nociceptive transmission of visceral (Brink and Mason, 2003, 2004; Brink et al, 2006) and trigeminal (Ellrich et al, 2000) inputs. Serotonergic cells are a separate group of RVM neurons defined by slow, regular discharge and distinct neurochemistry that appears to modulate autonomic activities (Potrebic et al, 1994; Mason, 1997, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The ventrolateral periaqueductal gray (vlPAG) is an important brainstem structure, exerting both inhibitory and facilitatory effects on pain perception [22; 24; 30; 37; 38]. The vlPAG modulates spinal cord nociceptive transmission via projections to the rostral ventral medulla (RVM), forming the PAG-RVM-spinal descending pain inhibitory network [16; 22].…”
Section: Introductionmentioning
confidence: 99%
“…The medullary dorsal horn (MDH) has been extensively investigated immunohistochemically in relation to the transmission, and modulation of orofacial nociceptive signals, especially lamina II [1,2]. Neurotensin (NT)-and enkephalin (ENK)-containing neurons, and nerve endings are present in the superficial layers of the MDH [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%